PENGARUH PENGGUNAAN PUPUK ORGANIK CAIR (LIMBAH SAYUR DAN BUAH) TERHADAP PERTUMBUHAN DAN HASIL TANAMAN TOMAT ( Lycopersicum esculentum) - Nge, Sonya Titin; Bullu, Novi Ivonne; Bouka, Elisabeth (UNIVERSITAS MUHAMMADIYAH METRO, 2024)
Lycopersicum esculentum is a horticultural plant that has many benefits. This study aims to determine the response to the use of liquid organic fertilizer (vegetable and fruit waste) on the growth and yield of tomato plants and to determine which treatment will give the best response to the growth and yield of tomato plants. This study was an experimental study designed using a completely randomized design (CRD) with 4 treatments and 4 replications. The data collection technique was carried out every 7 days after the tomato plants appeared on the ground, with the parameters observed being plant height (cm), number of leaves (strands), stem diameter (cm), flowering age, fruit number, and fruit weight (g). The data obtained from the growth of plant height, number of leaves, stem diameter at the last observation, and production yield of tomato plants was analyzed using variance (ANOVA) to determine whether there was a treatment effect and if there was a real or very significant treatment effect it would be followed by Duncan's test. at the 5% level to determine differences between treatment pairs being compared (Sastrosupadi, 2017). The results showed that the administration of POC from vegetable and fruit waste had a very significant effect on the growth and yield of tomato plants. The application of liquid organic fertilizer from papaya vegetable and fruit waste with a concentration of 18% gave optimum results for the growth and yield of tomato plants (Lycopersicum esculentum) where the average plant height was 41,75 cm, the number of leaves was 13, the stem diameter was 2.6 cm, number of fruit 8.5625 fruit and fruit weight 86.69 gram